Evolution of a Canada Basin ice‐ocean boundary layer and mixed layer across a developing thermodynamically forced marginal ice zone. Issue 8 (22nd August 2016) - Gallaher, Shawn G.; Stanton, Timothy P.; Shaw, William J.; Cole, Sylvia T.; Toole, John M.; Wilkinson, Jeremy P.; Maksym, Ted; Hwang, Byongjun
Abstract: A comprehensive set of autonomous, ice‐ocean measurements were collected across the Canada Basin to study the summer evolution of the ice‐ocean boundary layer (IOBL) and ocean mixed layer (OML). Evaluation of local heat and freshwater balances and associated turbulent forcing reveals that melt ponds (MPs) strongly influence the summer IOBL‐OML evolution. Areal expansion of MPs in mid‐June start the upper ocean evolution resulting in significant increases to ocean absorbed radiative flux (19 W m −2 in this study). Buoyancy provided by MP drainage shoals and freshens the IOBL resulting in a 39 MJ m −2 increase in heat storage in just 19 days (52% of the summer total). Following MP drainage, a near‐surface fresh layer deepens through shear‐forced mixing to form the summer mixed layer (sML). In late summer, basal melt increases due to stronger turbulent mixing in the thin sML and the expansion of open water areas due in part to wind‐forced divergence of the sea ice. Thermal heterogeneities in the marginal ice zone (MIZ) upper ocean led to large ocean‐to‐ice heat fluxes (100–200 W m −2 ) and enhanced basal ice melt (3–6 cm d −1 ), well away from the ice edge. Calculation of the upper ocean heat budget shows that local radiative heat input accounted for at least 89% of the observed latent heat losses and heat storage (partitioned 0.77/0.23). These results suggest that the extensive area of deteriorating sea ice observed away from the ice edge during the 2014 season, termed the "thermodynamically forced MIZ, " was driven primarily by local shortwave radiative forcing. Key Points: Thermodynamic evolution of the upper ocean directly responds to changes in surface sea ice conditions Melt pond expansion and drainage lead to significant increases in ocean heat storage and development of the summer mixed layer and NSTM The thermodynamic MIZ observed in the Canada Basin in late summer largely due to local radiative heat input